The effects of sex hormones on the size of intestinal lipoproteins - Nauli, Andromeda M.; Phan, Ann; Tso, Patrick; Nauli, Surya M. (Frontiers in Physiology, 2023)
Larger intestinal lipoproteins are more likely to be retained longer in the intestinal wall, allowing more time for their fat to be hydrolyzed and subsequently taken up by the abdominal viscera. Since men generally accumulate more abdominal visceral fat than women, we sought to determine if males produce larger intestinal lipoproteins compared to females. Using the conscious lymph fistula mouse model, we discovered that the male mice indeed produced larger intestinal lipoproteins than the female mice when they were intraduodenally infused with lipid emulsion. We then employed our differentiated Caco-2 cell model with semipermeable membrane system to determine the effects of sex hormones on the size of intestinal lipoproteins. Lipoprotein size was quantitatively measured by calculating the ratio of triglycerides (TG)/Apolipoprotein B (ApoB) and by analyzing their transmission electron micrographs. Our studies showed that while there was no dose-dependent effect of estrogen and progesterone, testosterone significantly increased the size of lipoproteins. When these hormones were combined to resemble the physiological concentrations observed in males and the different ovarian cycle phases in premenopausal females, both the male and luteal groups had significantly larger lipoproteins than the ovulatory group; and the male group also had significantly larger lipoproteins than the follicular group. The ovulatory group secreted a significantly lower amount of TG than the male and luteal groups. ApoB was comparable among all these groups. These findings support our hypothesis that, through their testosterone effects, males are more likely to produce larger intestinal lipoproteins. Larger lipoproteins tend to remain longer in the intestinal wall and may facilitate fat uptake preferentially by the abdominal viscera. Our studies may partly explain why men are more prone to accumulating abdominal visceral fat, which is an independent predictor of mortality.